2018
DOI: 10.1002/aenm.201703539
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Exfoliating and Generating Active Sites on Graphene Nanosheets Strongly Coupled with Carbon Fiber toward Self‐Standing Bifunctional Cathode for Rechargeable Zn–Air Batteries

Abstract: The self‐standing electrode nanomaterials with highly effective bifunctional electrocatalysis for oxygen reduction and evolution reactions (ORR/OER) are important for practical applications in metal–air batteries. Herein, a defect‐enriched and pyridinic‐N (PN) dominated bifunctional electrocatalyst with novel core–shell architecture (DN‐CP@G) is successfully fabricated by in situ exfoliating graphene from carbon paper followed by high temperature ammonia treatment. Benefitting from its strongly coupled core–sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(101 citation statements)
references
References 37 publications
5
96
0
Order By: Relevance
“…The graphene shells have abundant defect sites and active pyridinic‐N dopants, which are mainly responsible for generating efficient active sites for electrocatalytic reactions. Thus, owing to abundant defect sites, high content of pyridinic‐N, and strongly coupled core–shell structure, the electrode achieved high electrocatalytic activity and stability . Guo et al showed the use of carbon nanosheets containing dispersed Co–N x –B y –C could provide rich active sites as efficiency oxygen electrocatalysis for Zn–air batteries.…”
Section: Defect Engineering On Electrode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The graphene shells have abundant defect sites and active pyridinic‐N dopants, which are mainly responsible for generating efficient active sites for electrocatalytic reactions. Thus, owing to abundant defect sites, high content of pyridinic‐N, and strongly coupled core–shell structure, the electrode achieved high electrocatalytic activity and stability . Guo et al showed the use of carbon nanosheets containing dispersed Co–N x –B y –C could provide rich active sites as efficiency oxygen electrocatalysis for Zn–air batteries.…”
Section: Defect Engineering On Electrode Materialsmentioning
confidence: 99%
“…Thus, owing to abundant defect sites, high content of pyridinic-N, and strongly coupled core-shell structure, the electrode achieved high electrocatalytic activity and stability. [19] Guo et al showed the use of carbon nanosheets containing dispersed Co-N x -B y -C could provide rich active sites as efficiency oxygen electrocatalysis for Zn-air batteries. The introduced boron element gave deficient electron sites that activated the electron transfer around the Co-N-C sites and enhanced interaction with oxygen-containing substances, thus speeding up the reaction kinetics of 4e − processing of the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) (Figure 2c).…”
Section: Energy Storage Sites/adsorption Sites/active Sitesmentioning
confidence: 99%
“…[9,[356][357][358][359][360][361][362][363][364][365][366][367][368] but, the high cost, scarce resource, and poor durability of these metal-based catalysts have been disadvantageous for their widespread and large-scale applications in renewable energy technologies. [369][370][371] Additionally, flexible energy devices are attracting increasing attention because of their unique properties, including lightweight and malleable shape, which enable their use in bendable portable devices-of particular interest for the burgeoning wearables market. [372] Unfortunately, current oxygen electrodes are rigid and heavy, and the design of flexible electrodes requires materials with 3D architectures featuring outstanding oxygen electrocatalytic activity and excellent mechanical properties.…”
Section: D Carbons For Bifunctional Oxygen Electrocatalysis (Oer Andmentioning
confidence: 99%
“…Significantly, the RRDE measurement is very useful and often employed to quantify the ORR efficiency of catalysts . Figure d shows the percentage of H 2 O 2 yield obtained at the ring electrode due to the H 2 O 2 reduction.…”
Section: Resultsmentioning
confidence: 99%
“…Significantly,t he RRDEm easurement is very useful and often employed to quantify the ORR efficiency of catalysts. [54] Figure 5d shows the percentage of H 2 O 2 yield obtained at the ring electrode due to the H 2 O 2 reduction.A sc an be seen over the potential range from 0t o0 .8 V, Fe 3 C@N-CSs yields about 6.1 % À11.9 %H 2 O 2 ,w hich is better than 5.6 % À23.1 %f or Pt/C and 19.8 % À26.9 %f or N-CSs. Figure 5e shows the electron number transferred in three catalysts including Pt/C during ORR.…”
Section: Resultsmentioning
confidence: 99%